2008
DOI: 10.1176/appi.psychotherapy.2008.62.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy 2.0: MySpace® Blogging as Self–therapy

Abstract: A survey conducted by America Online (AOL®) in 2005 reported the startling finding that almost 50% of those posting entries on internet logs (weblogs or blogs), use them as a form of self-therapy. This finding went relatively unnoticed by psychotherapists and other mental health professionals. Given the rather significant global population ofbloggers (those who post internet journal entries) and readers, and the seemingly intractable problem of mental illness worldwide (according to the World Health Organisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 2 publications
1
28
0
Order By: Relevance
“…Efforts to analyze blogs have been hampered until recently by limitations in existing text analysis programs which are compromised by the ambiguities and repetitions of the informal, natural speech used by bloggers (for recent developments, however, see [94]). On face value, blogs seem to have potential health benefits, especially as adjuncts to psychological and behavioral treatments, as they encourage users to engage in reflection, knowledge sharing, and debate [95,96]. There are also suggestions that they also aid in the construction of meaning [97].…”
Section: Other Online Activitiesmentioning
confidence: 99%
“…Efforts to analyze blogs have been hampered until recently by limitations in existing text analysis programs which are compromised by the ambiguities and repetitions of the informal, natural speech used by bloggers (for recent developments, however, see [94]). On face value, blogs seem to have potential health benefits, especially as adjuncts to psychological and behavioral treatments, as they encourage users to engage in reflection, knowledge sharing, and debate [95,96]. There are also suggestions that they also aid in the construction of meaning [97].…”
Section: Other Online Activitiesmentioning
confidence: 99%
“…Sharing personal experiences with others has been proven to be helpful for peer-support, especially for those who have chronic illness [3]. The connection between the vlogger and the viewers is critical in health vlogs as past literature has shown that social support or connections with others work as self-therapy [36]. Despite the apparent advantages in further developing health vlogs, few studies have explored ways to improve patients’ connections with others in health vlogs.…”
Section: Introductionmentioning
confidence: 99%
“…The anonymity of the blog postings is a methodological asset in obtaining survivors’ authentic comments, including the reporting of sensitive information and adverse or negative events [36, 45, 46] blogging can be a coping strategy, a form of self-therapy, and a way to receive empathy and support from other bloggers [33, 39, 41, 42, 56, 62]. Collecting data from a public PC survivors’ blog is an invaluable strategy for revealing critical underlying issues while filling in psycho-oncology knowledge gaps about cancer cultures and patients’ view of cancer – for instance, as a social plague [63].…”
Section: Methodsmentioning
confidence: 99%